Mapping the barriers of AI implementations in the public distribution system: The Indian experience. (November 2021) - Kumar, Shashank; Raut, Rakesh D.; Queiroz, Maciel M.; Narkhede, Balkrishna E.
Abstract: With increasing digitization, private organizations have started adopting modern technology to improve the effectiveness and transparency of their system. In countries like India, where most public services are under government control, technology adoption is nascent due to various obstacles. The study considered artificial intelligence (AI) the most popular technology and identified 18 critical adoption barriers in India's public distribution systems (PDS). The study is further extended to find the contextual relationship among barriers using interpretative structural modeling (ISM) and prioritize them using the analytical network process (ANP) method. The study identifies lack of trust in technology, lack of AI literacy, and political issues as significant barriers to AI adoption in PDS. The hybrid methodology used in this study proposed five different strategies for effective and smooth implementation of AI in PDS, which would help the policymaker plan the same. Highlights: The Indian government is facing many challenges in operating the public distribution system (PDS). Eighteen critical barriers need to be removed for the effective adoption of AI. Time-based strategic planning is recommended for reducing the impact of barriers using hybrid research techniques.